2021
DOI: 10.1007/s40520-021-01821-2
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and limits of cancer treatment in an oldest old population

Abstract: Background Population of oldest old will grow dramatically in the next future and cancer, physiologically related to aging, will be very prevalent among them. Lack of evidence is a huge problem to manage cancer in oldest old and will be more and more in the next years. Aims Our purpose was to investigate the characteristics of a population of oldest old patients with cancer treated in the Radiation Oncology Unit of Fondazione Policlinico A. Gemelli IRCCS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Also, preventive drugs such as low-dose acetylsalicylic acid and statins are widely prescribed among participants with and without cancer. These findings are similar to those of studies showing that patients with cancer in an acute hospital setting continued to receive preventive medications, and even have preventive medications started near end of life [ 29 , 30 ]. Recent studies have shown that vitamin D supplementation in patients with cancer could have a positive impact [ 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…Also, preventive drugs such as low-dose acetylsalicylic acid and statins are widely prescribed among participants with and without cancer. These findings are similar to those of studies showing that patients with cancer in an acute hospital setting continued to receive preventive medications, and even have preventive medications started near end of life [ 29 , 30 ]. Recent studies have shown that vitamin D supplementation in patients with cancer could have a positive impact [ 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…Considering the increased comorbidities, decreased resilience to surgical stress, and vulnerability to poor nutrition of elderly patients, clinicians tend to choose conservative treatment, like chemotherapy, palliative therapy, or even only symptomatic treatment, instead of curative-intent surgery [ 16 ]. In fact, this frequently leads to the undertreatment of this patient population [ 17 ]. Recent studies have revealed that in the context of colorectal cancer, elderly patients derived equivalent oncologic outcomes to younger patients after radical surgery and concluded that age was not an independent prognostic factor for long-term survival [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, octogenarians are more likely to receive nonstandard care or be undertreated [69][70][71] because of their medical comorbidities, frailty, concern for treatment toxicity, or social determinants of health. Often performance status and comorbidities rather than cancer biology dictate the management strategy in elderly patients [72]. About half of early-stage breast cancer patients over 70 years old were reported to have sarcopenia [73].…”
Section: Discussionmentioning
confidence: 99%